(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Humanism is considered as most influential term and it is a moral and intellectual concept.Humanistic philosophy emphasis that all human beings are born with moral value, and have aresponsibility to help one another live better life.Rabindranath Tagore’s humanism and its significancein contemporary society are the focus of this study. The name Rabindranath Tagore is synonymouswith modern Indian literature, and it was he who first established modern India’s literary reputationaround the world. As one of India’s greatest literary masters, Tagore had a significant impact on thehistory of the Indian Renaissance in the early twentieth century. Tagore had a major impact on the riseof humanism in the early part of the twentieth centuryliterature. His personality and beliefs ofhumanism were shaped by a variety of factors. Interpersonal relationships are at the heart of Tagore’shumanism. Tagore’s theory of humanism is universal since it analyzes the universal nature andcreative existence of man. Rabindranath Tagore Philosophy of humanism can be studied in the light ofhis basic concept like Surplus in Man, concept of freedom and religion of man. The relevance of TagoreHumanism in today’s society shall be the topic of this paper.